(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Menarche is the first menstruation that adolescent girls attain. Menarche is one of the few indications of pubertal changes seen during adolescent phase accompanied by biological physical, and psychological changes. It marks the transitional phase of adolescent girls from child to being a teenager. It brought out the physiological development in girls and considered as landmarks in female puberty because it signifies the transformation from girlhood to womanhood. However the sudden occurrence of menstruation creates shame, fear, anxiety and uneasiness among adolescent’s girls. They also faced menstrual disorders such as abdominal pain, weakness, excessive bleeding, etc. Maintaining good hygiene during menstruation is also very necessary as lack of hygiene results in various health problems such as vaginal infections and reproductive tract infections. Mothers found to be the primary sources of information on menstruation. The role of mother is crucial in helping their daughters to manage their menstruation effectively. Proper awareness and education on menstrual health and hygiene is must. Thus the present study seeks to find mother’s awareness on menstrual health and hygiene. And also the role of mothers in communicating about hygiene practices to their daughters during menstruation in rural areas. How to cite this article: Singh AK. Menstrual Health and Hygiene: Awareness and Communication in Rural Areas. J Adv Res Jour Mass Comm 2018; 5(3): 33-39.